Pengaruh etika kerja islam terhadap kepuasan kerja dan komitmen organisasional (studi kasus cv kencana jaya teknik bogor) (IAIN Tulungagung, 2018)
This research explains the influence of Islamic work ethic toward satisfied occupation and organization commitment in CV Kencana Jaya Teknik Bogor. This research use quantitative method which take all of populations as a sample. Technique sample of this research use saturated sample which involve all Muslim employees as many 15 persons. Data collection technique use questionnaire has given as many 15 respondent persons. Data analysis technique in this research is simple regression analysis by t-test (partial) aid by SPSS application 16.0 version. Based on the result of the trial has done, that Islamic work ethic variable give positive influence significantly toward satisfied occupation and organizational commitment because the t- count higher than t- table, that is t- count for satisfied occupation has 4,113 < 2,160 (t table) and t- count for organizational commitment has 3,289 > 2,160 (t table) it means Islamic work ethic variable is significant partially with Islamic work ethic toward satisfied occupation and organizational commitment. Validity of that consideration supported by sig column in Islamic work ethic variable toward satisfied occupation has score 0,001 < 0,05 and Islamic work ethic toward organizational commitment has score 0,006 < 0,05. It shows that Islamic work ethic partially give influence for satisfied occupation and organizational commitment as significant.